Peningkatan Pengenalan Warna melalui Media Colour Cirle pada Kelompok A di Ra Aisyiyah Suruh Bringin Ngawi - Siti Nurkhasanah; Dita Primashanti Koesmadi; Wening Sekar Kusuma (Jurnal Syntax Admiration, 2024)
The purpose of this study was to find out how the color circle media in RA Aisyiyah Suruh bringin. to find out if the Colour circle media in Group A. This study uses a classroom action research model and points to the implementation process. The source of the research data was children aged 4-5 years in RA Aisyiyah Suruh, bringin, ngawi totaling 15 children, 5 women 10 boys. This data will be used for the purposes of research data analysis so as to recognize the picture of increasing colou circle color recognition in children aged 4-5 years. As a result, the learning process using color cirle media can improve problem-solving skills in Group A RA AISYIYAH Suruh, Bringin which was seen in the activities in cycle 1 with the theme of my environment sub-theme of God's creation with color recognition activities in children, in cycle 2 it was carried out with the theme of my environment sub-theme of God's creation with activities to introduce fruits and vegetables.